Site effects: assessing the fiscal, social and ecological costs of planned developments - Dittrich-Wesbuer, Andrea; Krön, Annette; Mayr, Alexander (Regional studies, regional science, 2015)
To achieve a more sustainable urban development it is necessary that decision-makers and others are able to understand the impacts of planned projects. To support this understanding a significant number of 'impact assessment tools' have been developed to facilitate decision-making for urban development. However, many of these tools have a rather narrow scope when looking at assessment areas or spatial scope. On that background, the research project RegioProjektCheck set out to develop an impact analysis tool with a broadened scope. Although the ambitious objectives had to be modified for some subject areas, the toolbox created can be seen as a starting point for a new generation of impact assessment tools that enable an integrated assessment. A new approach has also been attempted with wide distribution of the toolbox, providing free use and further technical development to anyone.